The Role of Community Reading Park as A Smart Solution in Increasing The Interest in Reading at Pamupukan Village - Rizqika Khumairaa; Irfan Fajrul Falah; Yani Suryani Cahyaningrum; Aisyah Paradilla; Rizqie Abu Chaery (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Good literacy skills positively impact various aspects of life, including education, economy, and participation in social life. However, interest in reading is still a serious problem in many countries, including Indonesia. To overcome this problem, reading parks was born as an effective solution. This service activity aims to describe the role of the community reading park (TBM NURUL ILMI) in Bakom hamlet, Pamupukan village, Ciniru, Kuningan district in increasing the reading interest of the Pamupukan community. The service model used is Community-Based Development. Data collection uses observation, interviews, and documentation. Participants in the service involved Asatidz and several residents of Bakom hamlet. Participants in the service involved 7 leaders in Pamupukun village and Bakom hamlet. With the TBM NURUL ILMI, students have a place or facility to increase students' interest in reading so that their literacy skills increase. This service implies that it is expected to be able to bridge students in Bakom village so that they are more active in reading to add broader insights and knowledge.